Liposomal microparticle injection can induce myeloid-derived suppressor cells (MDSC)-like cells in vivo. (4th May 2017) - Azuma, Hiroshi; Yoshida, Yoichiro; Takahashi, Hironori; Ishibazawa, Emi; Kobayashi, Hiroya; Sakai, Hiromi; Takahashi, Daisuke; Fujihara, Mitsuhiro
Abstract: Context: Myeloid-derived suppressor cells (MDSCs) are a subset of immature myeloid cells that function as immunosuppressive cells in various pathological conditions. Membrane-derived microvesicles are thought to be involved in MDSC induction. Earlier reports have described that injection of considerable amount of liposome into rat can suppress Con A-induced splenic T-cell proliferation. Liposome-internalized cells expressing CD11b/c suppress T-cell proliferation. Nitric oxide (NO) appears to be involved in the suppression. We speculated that, similarly to membrane-derived microvesicles, liposomal microparticles can induce MDSC-like cells in vivo . Objectives: To confirm our speculation we investigated dose-dependency of the suppressive effect, the effect of liposome on the induction of inducible NO synthase (iNOS), and anti-CD3 antibody-stimulated T-cell proliferation and cytokine production. Materials and methods: Liposome particles of 250 nm diameter were prepared and suspended in saline. Then, various amounts of liposomal suspension were injected intravenously into rats. After 24 h, rat spleens were removed and concanavalin A (or anti-CD3 antibody) stimulated-splenic T-cell proliferation and the production of iNOS, NO and cytokines were evaluated. Results: T-cell proliferation was suppressed dose-dependently by liposome injection. The immunosuppressive cell exerts its suppressive activity in a dose-dependent manner. The suppression was eliminated by iNOS inhibitor. iNOS was detected in liposome-loaded splenocytes. Anti-CD3 antibody-stimulated T-cell proliferation was also inhibited. Enhanced production of IL-10 was observed. Conclusions: Liposomal microparticles can induce MDSC-like cells in vivo . The lipids which comprise liposomes might serve an important role in the induction of MDSCs in vivo.